2022
DOI: 10.1364/boe.448135
|View full text |Cite
|
Sign up to set email alerts
|

First-in-clinical application of a time-gated diffuse correlation spectroscopy system at 1064 nm using superconducting nanowire single photon detectors in a neuro intensive care unit

Abstract: Recently proposed time-gated diffuse correlation spectroscopy (TG-DCS) has significant advantages compared to conventional continuous wave (CW)-DCS, but it is still in an early stage and clinical capability has yet to be established. The main challenge for TG-DCS is the lower signal-to-noise ratio (SNR) when gating for the deeper traveling late photons. Longer wavelengths, such as 1064 nm have a smaller effective attenuation coefficient and a higher power threshold in humans, which significantly increases the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 66 publications
0
20
0
Order By: Relevance
“…We have previously demonstrated the use of SNSPD detectors to effectively implement CW-DCS measurements at 1,064 nm for CBF measurements (Carp et al, 2020;Ozana et al, 2021). Recently, a time gated SNSPD enabled DCS system at 1,064 nm was also demonstrated in a case study on a patient with severe traumatic brain injury and showed good correlation of the DCS measurement with invasive perfusion monitoring (Poon et al, 2022). To our knowledge, in this report we present for the first time an optimized TD-DCS system with sufficient SNR at a late gate to enable brain functional activation measurements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously demonstrated the use of SNSPD detectors to effectively implement CW-DCS measurements at 1,064 nm for CBF measurements (Carp et al, 2020;Ozana et al, 2021). Recently, a time gated SNSPD enabled DCS system at 1,064 nm was also demonstrated in a case study on a patient with severe traumatic brain injury and showed good correlation of the DCS measurement with invasive perfusion monitoring (Poon et al, 2022). To our knowledge, in this report we present for the first time an optimized TD-DCS system with sufficient SNR at a late gate to enable brain functional activation measurements.…”
Section: Discussionmentioning
confidence: 99%
“…All these factors led to the choice of SNSPDs as detectors for our next-generation TD-DCS system. A similar approach, though without the ability to customize the laser pulse characteristics has recently been reported by Poon et al (2022) .…”
Section: Introductionmentioning
confidence: 99%
“…For 1064 nm DCS, we used an SNSPD that allows for optimal measurements and has started to emerge in the DCS field. 42,65,66 With a great range of possible imaging detectors, after surveying several possible camera detectors, we aggregated the properties into a CMOS camera with average values for read noise, number of pixels, frame rate, and quantum efficiency. The selection of these properties has great influence on the outputs of the model.…”
Section: Discussionmentioning
confidence: 99%
“…2 )? Here we describe three potential solutions, not mutually exclusive, that are being investigated: first, enhancing SNR by further increasing the speckle number, based on parallelizing multiple cameras for iDWS/MiDWS, is a straightforward way to achieve larger S–C separation (i.e., higher brain specificity); second, combining iDWS with coherence gating, to filter out extracerebral photons with short TOFs at a small S–C separation, can improve both SNR (more cerebral photons) and brain specificity; 39 , 41 , 43 third, the intrinsic advantages of SNR and high source power for DCS at 1064 nm can be carried over to interferometric detection, 61 , 62 in which extremely costly 1064 nm photon counting detectors 63 can be replaced by InGaAs cameras, 64 which are less costly.…”
Section: Limitations Questions and Issues To Be Solvedmentioning
confidence: 99%